NARRATING THE ACT OF TRUTH IN THE JATAKA AND AVADANA RELIEFS AT CANDI BOROBUDUR - LEE, So Tju Shinta (UI Scholars Hub, 2023)
This paper analyzes the Act of Truth in nine Jataka and Avadana stories depicted in Candi Borobudur, Central Java, aiming to identify its key factors and purpose in the allegories. Through content analysis and comparative analysis, the study finds that merit, right speech, and intention are the primary contributing factors to the Act of Truth. A beneficial Act of Truth involves taking a firm stance on truth, driven by compassion to benefit others and attain one’s highest potential. The findings suggest that the acts in these stories form a part of the bodhisattva’s path to achieving perfect awakening. This study also offers insights into the beneficial acts represented in ancient Javanese reliefs.